The Art of Ethics in the Information Society. Mind you - Janssens, Liisa (Amsterdam University Press, 2016)
New technologies are often implemented before their ethical consequences have been fully understood. In this volume, experts working in the sciences, arts, and philosophy of technology share novel perspectives on how we can